Impact Of Technological, Organizational And Environmental Factors On Intention To Continue Using B2b E-Commerce By Small And Medium Enterprises (Smes) In Jordan - Sarhan, Lubna Abdulhussein (2018)
The adoption of electronic commerce (e-commerce) for the Business to Business (B2B) business model category in business operations is currently no longer a privilege merely to large organizations; the small and medium enterprises (SMEs) can also benefit from the adoption. Although the SMEs are considered to play a major role in the economic growth for most nations, they are generally moving slower towards adopting B2B e-commerce compared to larger organizations. Subsequently this makes SMEs more susceptible to any changes in the economic conditions as they would have relatively low levels of competitiveness. It is important to determine the factors influencing intention to continue using B2B ecommerce by the SMEs so that they can effectively use it without wasting their limited resources. Many studies have been done on the adoption of B2B e-commerce but most of them focus on large organizations. Therefore, this study aims to examine the factors that effect the intention to continue using B2B e-commerce among the manufacturing SMEs in Jordan using the Technological, Organizational and Environmental Model (TOE) that has been developed by Tornatzky and Fleischer. The quantitative method has been applied in this study where data collection has been done using self-administrated questionnaire distributed to the SMEs in the manufacturing sector in Amman. The total number of valid questionnaires is 251, constituting a response rate of 55.8%.